Sosialisasi dan Penerapan Pembukuan Transaksi Digital Menggunakan Excel pada Anggota dan Bendahara PKK Padukuhan Tritis di Desa Ngargosari - Swastikasari, Adelia; Yendrawati, Reni; Kartini (Rahmatan Lil ’Alamin Journal of Community Services, 2023)
In the digital era, there is a push for the community to be able to operate technology. This work program discusses the importance of keeping up with developments in the Digitalization Era. Digitalization brings new challenges and opportunities in terms of transaction accounting. Digital transaction accounting using Excel is considered an effective way to manage financial records. While there are drawbacks to manual accounting, authors aims to provide understanding to the community of Padukuhan Tritis about the use of the internet in PKK activities and introduces digital transaction accounting. Despite limited internet signal issues in Padukuhan Tritis, observation results show progress in using Excel for recording cash and loan transactions. This program is expected to raise awareness among the community about digital systems, especially in finance, and support the PKK treasurer in financial recording.